An efficient t-BuOK promoted C3-chalcogenylation of indoles with dichalcogenides. Issue 27 (27th June 2018) - Yu, Yuanzu; Zhou, Yan; Song, Zengqiang; Liang, Guang
Abstract : A practical route to prepare 3-sulfenyl- and 3-selenyl-indoles has been achieved using t -BuOK as a promoter at room temperature. Abstract : A versatile and efficient method for the synthesis of 3-chalcogenyl-indoles from indoles and dichalcogenides employing t -BuOK as a promoter at room temperature has been achieved. The present protocol exhibited a broad functional group tolerance. Diverse 3-sulfenyl- and 3-selenyl-indoles were rapidly obtained in good to excellent yields with high regioselectivities. It is noteworthy that this transformation was applicable to N -protected and N -unprotected indoles, allowing N -deprotection and C3-chalcogenylation of indoles in one step.